2021
DOI: 10.1002/suco.202100102
|View full text |Cite
|
Sign up to set email alerts
|

Predictive model for slenderness limit of circular RC columns confined with FRP wraps

Abstract: Application of fiber-reinforced polymer (FRP) for retrofitting and rehabilitation of concrete structures is a common method. The main role of FRP confinement for reinforced concrete (RC) columns is to increase the ultimate strength and strain of confined concrete core and therefore improve in the load carrying capacity of the columns. However, it is possible that a previously short column fails due to buckling after the application of FRP confinement. In other words, the enhanced compressive strength of a retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 81 publications
(138 reference statements)
0
2
0
Order By: Relevance
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/undamaged concrete structures 1–8 . To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed 9–18 .…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that fiber reinforced polymer (FRP), such as aramid fiber reinforced polymer (AFRP), basalt fiber reinforced polymer (BFRP), carbon fiber reinforced polymer (CFRP) and glass fiber reinforced polymer (GFRP), can significantly improve the load bearing and deformation capacity of damaged/undamaged concrete structures 1–8 . To accurately predict the load bearing capacity of damaged concrete after FRP strengthening, many compressive strength models have been proposed 9–18 .…”
Section: Introductionmentioning
confidence: 99%
“…In developing fibre-reinforced plastics (FRP) materials, different FRP techniques have been developed and used because of their distinct properties, such as high tensile capacity, high strength-to-weight ratio, and easy handling; however, FRP also has some disadvantages, such as inappropriate use in fire environments, wet surfaces, and inadequate bonding with concrete surfaces. Additional treatment is required to counter these environments [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%